2019
DOI: 10.1021/acs.jcim.9b00497
|View full text |Cite
|
Sign up to set email alerts
|

Residence Time Prediction of Type 1 and 2 Kinase Inhibitors from Unbinding Simulations

Abstract: Supporting Information. Biological data of the inhibitors, details on computational method, computing time, Movie of unbinding process of B96 from one replicate, Tables S1-S2, and Figures S1-S6. This material is available free of charge via the Internet at http://pubs.acs.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
4
19
0
1
Order By: Relevance
“…From the loading plot, it can be deduced that larger molecular volume contributes to longer residence time, while stronger hydrophilic interactions contribute to faster dissociation (Figure 7d). The result proposed in this study is consistent with previous researches, which suggested that type I kinases inhibitors bind to the ATP binding site and usually smaller and faster, while compounds of type II are generally large since occupy additional transient sub-pocket [36,37].…”
Section: Volsurfsupporting
confidence: 92%
See 1 more Smart Citation
“…From the loading plot, it can be deduced that larger molecular volume contributes to longer residence time, while stronger hydrophilic interactions contribute to faster dissociation (Figure 7d). The result proposed in this study is consistent with previous researches, which suggested that type I kinases inhibitors bind to the ATP binding site and usually smaller and faster, while compounds of type II are generally large since occupy additional transient sub-pocket [36,37].…”
Section: Volsurfsupporting
confidence: 92%
“…After variable selection and PLS modeling, an optimal PLS model with two variables was obtained, of which R 2 , Q 2 and R 2 val for k off are 0.821, 0.818 and 0.821, respectively (Table 4). As showed in Table 5, it can be seen that the prediction performances of the VolSurf model is superior to that of the models based on position-restrained MD [15] and biased MD simulations [36]. Furthermore, the results of 1000-repeated PLS modeling and 500-times Y-random permutations test demonstrates that the high-quality PLS model is not caused by accident ( Figure 6).…”
Section: P38 Mitogen-activated Protein Kinasementioning
confidence: 89%
“…The barrier heights from this potential of mean force for each ligand were then used to predict the dissociation rate, and a high correlation of 0.86 with the experimental dissociation rate was observed. However, this method was relatively expensive computationally, requiring a total of 4.5 µs for each ligand [43].…”
Section: Introductionmentioning
confidence: 99%
“…A method combining steered molecular dynamics (SMD) and computation of free energies of dissociation obtained R 2 te of 0.88 for a dataset comprised of eight inhibitors. 72 In another study, a model obtained using PLS regression, a training set of 14 inhibitors, a test set of 6 inhibitors and protein-inhibitor interaction fingerprints (IFPs) from simulations of inhibitor dissociation had R 2 te of 0.56 and R 2 tr of 0.72. 73 Negative binding energy integrals obtained from ligand dissociation using local-scaled MD achieved R 2 te of 0.64 in the prediction of k of f values for 41 complexes with different kinases, including 12 complexes with p38 MAP kinase.…”
Section: Discussionmentioning
confidence: 99%